2019
DOI: 10.1016/j.yebeh.2019.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Possible epigenetic regulatory effect of dysregulated circular RNAs in epilepsy

Abstract: Circular RNAs (circRNAs) involve in the epigenetic regulation and its major mechanism is the sequestration of the target micro RNAs (miRNAs). We hypothesized that circRNAs might be related with the pathophysiology of chronic epilepsy and evaluated the altered cir-cRNA expressions and their possible regulatory effects on their target miRNAs and mRNAs in a mouse epilepsy model. The circRNA expression profile in the hippocampus of the pilocarpine mice was analyzed and compared with control. The correlation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…A large number of reports have shown that circular RNAs affect miRNA-mediated regulation of gene expression through miRNA sequestration [20]. In order to better excavate the circRNAs involved in the pathogenic mechanism of CV-A16 infection, we selected circRNAs related to "Immune system process" in GO-BPs analysis and circRNAs related to "In ammation mediated by chemokine and cytokine signaling pathway" in KEGG analysis.…”
Section: Prediction Of Circrna-mirna-target Gene Associationsmentioning
confidence: 99%
“…A large number of reports have shown that circular RNAs affect miRNA-mediated regulation of gene expression through miRNA sequestration [20]. In order to better excavate the circRNAs involved in the pathogenic mechanism of CV-A16 infection, we selected circRNAs related to "Immune system process" in GO-BPs analysis and circRNAs related to "In ammation mediated by chemokine and cytokine signaling pathway" in KEGG analysis.…”
Section: Prediction Of Circrna-mirna-target Gene Associationsmentioning
confidence: 99%
“…Most studies on circRNA expression in neuronal diseases correlates the circRNA expression profile with miRNA and mRNA profiles ( Table 2 ). Disease-regulatory networks of circRNA-miRNA-mRNA are bioinformatically extracted, by the identification of microRNAs targeting the circRNA sequences with an opposite differential expression, and the miRNA target mRNA with a regulation similar to circRNA [ 81 , 90 , 93 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. Based on the presence of one to seven miRNA target sequences on the circRNA, the decrease in miRNA levels is associated with the observed increase in the cognate circRNA levels through a sponge mechanism, in which circRNAs act as competing endogenous RNAs [ 124 , 125 , 126 , 127 ].…”
Section: Neuronal Circrnasmentioning
confidence: 99%
“…Epilepsy is a destructive neurological disease characterized by repeated spontaneous seizures, which have serious health and economic burdens, and greatly reduce the quality of life for those affected. [1][2][3][4] This common chronic neurological disease affects almost 50 million people worldwide. 5 Regardless of the type of primary injury, common pathological reactions occur around the damaged brain tissue during the incubation period, forming an abnormal neural network and resulting in neuronal synchronization overexcitation.…”
Section: Introductionmentioning
confidence: 99%